Superior Adhesion of a Multifunctional Protein‐Based Micropatch to Intestinal Tissue by Harnessing the Hydrophobic Effect. Issue 6 (23rd April 2022) - Yamazoe, Hironori; Kominami, Chizuko; Abe, Hiroko
Abstract: Drug delivery systems comprising drug carriers capable of adhering to intestinal tissue have considerable potential to realize more sophisticated systemic drug delivery and topical drug treatments in the intestinal tract. The development of innovative strategies for improving the adhesion efficiency of carriers is of high importance for the advancement of this field. Herein, a novel approach to achieving high adhesion efficiency of drug carriers is presented, where the accessibility of the carrier to the intestinal surface and its subsequent adhesion to the intestinal tissue are promoted by utilizing the thermodynamic tendency of the hydrophobic carrier and its dispersion solvent, triacetin, to be excluded from the aqueous environment. Drug carriers are fabricated using proteins, imparting multiple functions, including drug release and the removal of reactive oxygen species (ROS). Results of ex vivo studies indicate that this multifunctional protein‐based carrier, "protein micropatch, " adheres to various mouse intestinal tissues, including the small intestine, colon, and inflamed colon, with high efficiency. Furthermore, protein micropatches, administered to mice via oral or rectal routes, successfully adhere to the intestinal tract. This approach and the highly functionalized carrier described in the study have the potential to significantly contribute to the development of bioadhesive carrier‐based drug delivery systems. Abstract : Drug carriers capable of adhering to the intestinal tract are useful for systemic drug delivery and topical drug treatment. Novel strategies for improving the adhesion efficiency of carriers and creating highly functionalized carriers are presented. Remarkable adhesion of the constructed protein‐based multifunctional carriers to intestinal tissue is demonstrated under ex vivo and in vivo conditions using a mouse model.